Land Tenure Conflicts in Forest Areas of Muara Gembong, Bekasi Regency - Nugroho, Adi Purwanto; Sunito, Melani Abdulkadir; Kinseng, Rilus A (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Land tenure conflicts have been a significant problem in Java for decades. The divergence between the state’s legal view and the community’s historical claim to land rights has sparked longstanding debate. This study aims to describe the dynamics of land tenure through empirical evidence of the historical trajectory of land tenure in forest areas in Muara Gembong District, Bekasi Regency. The research was conducted using in-depth interviews, analysis of historical data and literature, and a review of relevant land and forest policy documents. As a result, land tenure policies by the State only gain legal certainty without the legitimacy of local communities. The findings reveal that the land tenure dynamics in Muara Gembong are shaped by a process of state territorialization through the authority of the forestry sector, which is countered by local communities and regional authority efforts at counter-territorialization. This tension has led to tenure insecurity for local communities, as they often lack formal proof of land ownership. The presence of a forest area governance regime that relies on a top-down, command-and-control approach has proven ineffective in achieving its goal of maximizing public welfare. Therefore, future policy directions should focus on inclusive negotiation processes and reforms that ensure tenure security recognized by all parties.